Manipulations of micro/nanoparticles using gigahertz acoustic streaming tweezers - Hang Wu; Zifan Tang; Rui You; Shuting Pan; Wenpeng Liu; Hongxiang Zhang; Tiechuan Li; Yang Yang; Chongling Sun; Wei Pang; Xuexin Duan (Nanotechnology and Precision Engineering, 2022)
Contactless acoustic manipulation of micro/nanoscale particles has attracted considerable attention owing to its near independence of the physical and chemical properties of the targets, making it universally applicable to almost all biological systems. Thin-film bulk acoustic wave (BAW) resonators operating at gigahertz (GHz) frequencies have been demonstrated to generate localized high-speed microvortices through acoustic streaming effects. Benefitting from the strong drag forces of the high-speed vortices, BAW-enabled GHz acoustic streaming tweezers (AST) have been applied to the trapping and enrichment of particles ranging in size from micrometers to less than 100 nm. However, the behavior of particles in such 3D microvortex systems is still largely unknown. In this work, the particle behavior (trapping, enrichment, and separation) in GHz AST is studied by theoretical analyses, 3D simulations, and microparticle tracking experiments. It is found that the particle motion in the vortices is determined mainly by the balance between the acoustic streaming drag force and the acoustic radiation force. This work can provide basic design principles for AST-based lab-on-a-chip systems for a variety of applications.